Diseño del Sistema de Iluminación para el Estadio de Fútbol de la Liga Deportiva Cantonal de Catamayo - Lamas Tamayo, Marlon Polivio (2023)
In the present titling work, the lighting design and dimensioning was carried out for the stadium of Liga Deportiva Cantonal de Catamayo, the same one that was carried out according to the lighting recommendations of the Regulations of the International Federation of Associated Football (FIFA). It will be extinguished as a lighting design proposal using LED technology, considering that the luminaires will meet the necessary operating characteristics. For the simulation of the lighting system, the DIALux evo ® software was shown, so that the start-up of the lighting system can be observed graphically, as well as the results that ensure compliance with the FIFA Regulations. The economic analysis was carried out by calculating unit prices, determining the total cost of implementing the lighting system. Keywords: Photometric curves, sports luminaires, calculation of luminaires, DIALux evo ® software, electrical circuits, costs.